Production Planning in Custom Furniture: A Case Study of Sabar Furniture Without Interior Designer Involvement - 'Aisy, Nadhifia Iryadini Rohadatul; Candradewi, Silvya Bintang Ayu (Lembaga Penelitian dan Pengabdian kepada Masyarakat UPJ, 2025)
The home industry, particularly the furniture sector, is experiencing rapid growth in Indonesia, in line with increasing consumer interest in unique and personalized customization products. However, this industry continues to face significant challenges, including a lack of collaboration with interior designers and technical limitations in meeting consumer requirements. This study aims to analyze the production planning process at Sabar Furniture, a furniture industry specializing in custom furniture, particularly for products produced without the involvement of interior designers, to identify the challenges and strategies employed to address them. This research employs qualitative methods and case studies to explore production planning challenges at Sabar Furniture. The results show that production planning at Sabar Furniture is conducted in a structured manner and is capable of implementing adaptive, order-based (made-to-order) production planning. However, in terms of function and aesthetics, the product will be more optimal if the production process involves collaboration between artisans and interior designers. This study offers insights into the importance of collaboration between artisans and designers in the household furniture industry, aiming to enhance product quality, achieve customer satisfaction, and address the rapid development challenges in the furniture sector.